Preparation and Performance of ZnO and ZnO/MnO2 Nanostructures as Anode Electrodes in DSSCs - Suaad Abd Mahdi Abd Noor; Amer Muosa Juda Al-Shamari (Indonesian Journal of Chemistry, 2023)
Nanoparticles and nanocomposites prepared by the hydrothermal method (ZnO, ZnO/MnO2) were used to build dye-sensitized solar cells (DSSCs), which were used as photoelectrodes using two natural dyes as the absorbent media: red (Hibiscus sabdariffa) and green (Apium graveolens). The results showed the efficiency of the green dye in DSSCs is superior to the red dye in terms of conversion efficiency (η). The purpose of the study is to improve the performance of dye solar cells. The properties of nanomaterials were studied by X-ray diffraction (XRD), scanning electron microscopy (FE-SEM), and transmission electron microscopy (TEM) for the analysis of ZnO NPs and ZnO/MnO2, whereas the sizes of the prepared materials are within the size of 1–100 nm. The solar cell parameters were obtained from simple (I-V) measurements for nanomaterials prepared using two-dye DSSCs where Isc represents the short circuit current through the solar cell when the voltage across the solar cell is zero, and Voc represents the open circuit voltage across the solar cell and is the maximum voltage available from the solar cell. The photoelectrochemical properties of the two dye DSSCs in this study were calculated at 22.53 mW/cm2 of the light intensity.